Double chambered right ventricle with ruptured sinus of Valsalva: rare entity - Lalwani, Jaya; Kumar, Lokesh; ., Rameshwar; M., Jagadeesan (International Journal of Advances in Medicine, 2022)
Valsalva sinus aneurysm (SVAs) and double-chambered right ventricle (DCRV) is an uncommon congenital heart defect and are usually associated with ventricular septal defect (VSD) in 50% to 60% of patient’s population. The current case report had documented a 59 years old hypertensive asymptomatic male with a known case of SVAs presented to our hospital following device closure for 6 months. On examination, the patient was diagnosed to have DCRV induced by SVAs prior to the closure along with other factors. However, to the best of our knowledge, this is the first case report on DCRV induced by SVAs in synergy with other associated multifactors and without VSD among the Indian population.